The Bahamas : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper assesses the recent trends in The Bahamas' offshore financial center (OFC) and their contribution to the real economy. The Bahamas hosts one of the largest OFCs in the world. International banks are the most important institutions in the Bahamian OFC. Despite a sharp contraction in the size of the offshore sector, the direct impact on the real economy appears to have been modest. The direct contribution of offshore banks to the real economy appears to have remained broadly stable, reflecting an orderly adjustment so far. Strong compliance with anti-money laundering and combating the financing of terrorism and tax transparency standards should help ensure that this orderly adjustment continues.